1999
DOI: 10.1136/hrt.81.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy in women with congenital shunt lesions

Abstract: Objective-To evaluate the outcome of pregnancy in women with congenital shunt lesions. Setting-Retrospective study in a tertiary care centre. Methods-Pregnancy history was obtained by a standardised questionnaire and medical records were reviewed. Patients-175 women were identified, at a mean (SD) age of 42 (14) (Heart 1999;81:271-275)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 22 publications
6
48
1
4
Order By: Relevance
“…3,4 In the present study we found a low rate of cardiac events during pregnancy, which is in agreement with the small amount of existing literature. [5][6][7][8] The risk of obstetric events was associated with the corrective status. The presence of an unrepaired VSD was associated with a higher risk of pre-eclampsia (8.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In the present study we found a low rate of cardiac events during pregnancy, which is in agreement with the small amount of existing literature. [5][6][7][8] The risk of obstetric events was associated with the corrective status. The presence of an unrepaired VSD was associated with a higher risk of pre-eclampsia (8.7%).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Despite the fact that a VSD is one of the most common forms of heart disease among pregnant women, VSD-specific pregnancy data are limited. [5][6][7][8] A recent literature review of studies published between 1985 and 2007 found a total of 83 completed pregnancies among women with VSDs (combining repaired and unrepaired VSD). 9 The current consensus is that pregnancy in women with an isolated VSD is generally well tolerated, with no maternal mortality and no significant maternal or fetal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal outcome is also good in rheumatic heart disease but in cyanotic heart disease there is increased fetal loss. 9 With improved medical care, surgical correction of congenital lesion and better obstetrical care, maternal and fetal mortality and morbidity have been reduced markedly.…”
Section: Discussionmentioning
confidence: 99%
“…(25)(26)(27) Mitral valve prolapse is no contraindication for pregnancy. (27) Medium or high-risk pregnancy includes women with 1) prosthetic valves; 2) obstructive lesions, including uncorrected coarctation of the aorta; 3) Marfan syndrome or other aortic disorders; 4) cyanotic CHD; 5) pulmonary hypertension; 6) systemic ventricular dysfunction (ejection fraction <40%), or 7) signifi cant uncorrected CHD (see Table II).…”
Section: Principles Of Management Of Pregnancy In Women With Chdmentioning
confidence: 99%